The challenges of implementing the enforcement system in the Republic of North Macedonia: Array - Etemi-Ademi, Bukurije; Zendeli, Emine (Acta Universitatis Danubius. Juridica, 2021)
Prior to the establishment of the private enforcement system in the Republic of North Macedonia, a number of problems related to the efficiency of the enforcement system, for which the basic courts were competent, were evident. In order to overcome the problems of this system with special emphasis on the duration and overload of courts with cases, the concept of private enforcement was introduced. This solution of the legislator brought with it a series of reactions in the public, especially when it comes to the complete privatization of the enforcement procedure that our country accepted. The attitude of the Ministry of Justice of the RNM regarding the functioning of the private enforcement system are quite positive, while on the other hand citizens express dissatisfaction with the private form of enforcement. Citizens are less likely to turn to the court for a decision on legal remedies, as the court has jurisdiction to decide on them. Taking into consideration the abovementioned issue, this paper attempts to analyze the enforcement system in the RNM, by presenting the efforts of our country to create a legal framework for efficient enforcement procedures, as well as presenting the experiences and attitudes of the RNM citizens on their perceptions about the current enforcement system.